The Influence of Adoption Digitally-Enabled Circular Strategies on the Economic Efficiency of MSMEs in Batam City - So, Vincent; Eryc, Eryc (SIMAK, 2025)
This study aims to analyse the effect of digital-based circular economy strategy adoption on the economic efficiency of Micro, Small, and Medium Enterprises (MSMEs) in Batam City. Using descriptive quantitative method and multiple linear regression analysis, this study involved 311 respondents from MSMEs in Batam City. The results showed that both circular economy and digitalization have a positive and significant effect on the economic efficiency of MSMEs by 38.8%. Circular economy helps reduce waste and optimize resources, while digitalization supports operational efficiency through automation and technological innovation. The combination of these two approaches can create a sustainable business ecosystem and improve the global competitiveness of MSMEs. However, challenges such as limited digital literacy, technological infrastructure, and resistance to change remain major obstacles. This research provides important insights for the development of policies and practices that support digital transformation and circular economy in MSMEs, particularly in Batam City.